2020
DOI: 10.3855/jidc.11625
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Rickettsia africae in Amblyomma ticks collected in cattle from Southern and Central Mozambique

Abstract: Introduction: Rickettsia are Gram-negative and obligate intracellular bacteria, which cause typhus and spotted fever-like diseases in humans. In Africa, Rickettsia africae of the Spotted Fever Group Rickettsia (SFGR) is the etiologic agent of the African Tick-Bite Fever. The disease is transmitted by ticks of the genus Amblyomma, which serve as vectors and reservoirs of Rickettsia. In this study, we aimed to detect Rickettsia species in ticks collected from cattle in south and central Mozambique. Methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…africae in Amblyomma ticks is consistent with previous studies from southern Africa. While most of these studies only tested the infection rate for the adult life stage, our prevalence range of 52–90% in larvae is comparable to that found in adults (60–80%) [ 24 , 28 30 , 48 ]. This result provides evidence that the proportion of infected individuals remains relatively constant over both life stages and generation, suggesting efficient transstadial and transovarial transmission in nature.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…africae in Amblyomma ticks is consistent with previous studies from southern Africa. While most of these studies only tested the infection rate for the adult life stage, our prevalence range of 52–90% in larvae is comparable to that found in adults (60–80%) [ 24 , 28 30 , 48 ]. This result provides evidence that the proportion of infected individuals remains relatively constant over both life stages and generation, suggesting efficient transstadial and transovarial transmission in nature.…”
Section: Discussionsupporting
confidence: 67%
“…Rickettsia africae infection in A . hebraeum is high, typically ranging from 60–80% [ 26 30 ]. Previous studies testing for R .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was assumed Rickettsia spp. would dominate the samples as A. hebraeum is the principal vector of R. africae , evidently the study conducted by Magaia et al [ 28 ] confirmed that 80% of A. hebraeum ticks were infected with R. africae in Mozambique. As with other taxa presented in this study, nymphs had a higher relative abundance of Rickettsia spp.…”
Section: Discussionmentioning
confidence: 92%
“…Transstadial and transovarial transmissions of R. africae have been reported for A. hebraeum ( 145 , 146 ). A recent PCR analysis identified that most Amblyomma ticks (up to 100%) collected from cattle in south and central Mozambique are infected with R. africae ( 143 ). Similarly, R. africae infection was prevalent in A. variegatum ticks (87%) on cattle in Madagascar ( 147 ).…”
Section: Notable Emerging Sfg Rickettsia Species W...mentioning
confidence: 99%